Robustness and risk evaluation of bridge falsework structures - André, J. (2014)
Bridge falsework systems are one of the most common temporary structures used in the construction industry, namely to support the formwork during the construction, rehabilitation or retrofit works of concrete bridges and viaducts. A key contribution of this paper is to propose a novel risk management methodology based on newly developed robustness and fragility indices. Advanced stochastic investigations are carried out, in which the key variables that control the stochastic behaviour of bridge falsework systems are identified. Possible strategies to increase robustness and decrease fragility are discussed. The information gathered in this paper can be used to develop more rational and reliable bridge falsework structures thus safer and more design efficient.